2007
DOI: 10.2500/ajr.2007.21.3019
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery in Patients Receiving Anticoagulant or Antiplatelet Therapy

Abstract: ESS is a safe procedure when performed in patients receiving anticoagulation or antiplatet therapy, and could be classified as a moderate bleeding risk surgery. Stopping the medication prior to the surgery is mandatory. However, anticoagulation could be resumed early postoperatively because it does not seen to increase the risk for bleeding. Perioperative bridging with heparin should only be dictated by the patient's condition, not by the procedure itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In the otolaryngology literature, a case control study of sinus surgery patients found no increased blood loss in patients on baseline antithrombotic therapy. However, all patients in this study had therapy stopped at least 2 weeks prior to surgery, thereby eliminating any therapeutic effect at the time of surgery …”
Section: Discussionmentioning
confidence: 99%
“…In the otolaryngology literature, a case control study of sinus surgery patients found no increased blood loss in patients on baseline antithrombotic therapy. However, all patients in this study had therapy stopped at least 2 weeks prior to surgery, thereby eliminating any therapeutic effect at the time of surgery …”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are commonly used pre‐operatively to decrease infection and inflammation, although there are no trials that show whether they have an effect on surgical conditions or blood loss. Cessation of anticoagulation and antiplatelet medication is recommended, 17 but the risks of stopping these medications must be carefully considered 18–20 . Particular care is required in the setting of coronary stenting and the cessation of antiplatelet medications 18–22 and consultation with cardiology is recommended before scheduling surgery or ceasing antiplatelet medications 18–22 .…”
mentioning
confidence: 99%
“…The authors concluded that stopping anticoagulation or antiplatelet therapy is mandatory before the surgery, but the medication could be resumed in the early postoperative period without increasing the risk for bleeding. 16 Di Girolamo et al conducted a retrospective chart review in 110 hematologic patients with rhinosinusitis. Seventy one percent of the patients had severe thrombocytopenia (platelet count <50 000) and the remaining had mild to moderate thrombocytopenia except for two patients without thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%